People, places and landscapes social change in high amenity rural areas - Krannich, Richard S. (Landscape Series, 2011)
This volume is a cogent empirical analysis of the interplay between a region?s natural amenities and its socioeconomic  evolution. It focuses on the rural sectors of America?s Intermountain West region, which lies between the Cascades and Sierra Nevada mountains to the west and the Rocky Mountains to the east. Coherently structured and meticulously detailed, it adds much to our understanding of the ways an area?s forests, lakes, mountains, parkland and historic attractions affect residents? sense of well-being as well as the sociodemographic and economic changes they experience. The book examines patterns of growth and change linked to the emergence of New West? conditions, assessing their implications for the wider community as well as discussing the impact these trends could have on the consumption of natural resources. It also points to ways in which communities and their development can be managed sustainably.   The tight geographical focus of this valuable resource ensures a depth of analysis which can be applied to similar regions worldwide. Based on a large-scale, random-sample survey of both full-time and seasonal residents, it provides a much-needed overview of the macro-level economic, demographic, and social transformations affecting rural communities in America. As such, the book has relevance for all researchers concerned with rural development, the changes impacting rural landscapes, and natural resource management.